Impact of decitabine on immunohistochemistry expression of the putative tumor suppressor genes FHIT, WWOX, FUS1 and PTEN in clinical tumor samples - Stewart, David J; Nunez, Maria I; Jelinek, Jaroslav; Hong, David; Gupta, Sanjay; Aldaz, Marcelo; Issa, Jean-Pierre; Kurzrock, Razelle; Wistuba, Ignacio I (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Since tumor suppressor gene function may be lost through hypermethylation, we assessed whether the demethylating agent decitabine could increase tumor suppressor gene expression clinically. For fragile histidine triad (FHIT), WW domain-containing oxidoreductase (WWOX), fused in sarcoma-1 (FUS1) and phosphatase and tensin homolog (PTEN), immunohistochemistry scores from pre- and post-decitabine tumor biopsies (25 patients) were correlated with methylation of the long interspersed nuclear element-1 (LINE-1) repetitive DNA element (as a surrogate for global DNA methylation) and with tumor regression. Results With negative staining pre-decitabine (score = 0), the number of patients converting to positive staining post-decitabine was 1 of 1 for FHIT, 3 of 6 for WWOX, 2 of 3 for FUS1 and 1 of 10 for PTEN. In tumors with low pre-decitabine tumor suppressor gene scores (≤150), expression was higher post-treatment in 8 of 8 cases for FHIT (P = 0.014), 7 of 17 for WWOX (P = 0.0547), 7 of 12 for FUS1 (P = 0.0726), and 1 of 16 for PTEN (P = 0.2034). If FHIT, WWOX and FUS1 were considered together, median pre- versus post-decitabine scores were 60 versus 100 (P = 0.0002). Overall, tumor suppressor gene expression change did not correlate with LINE-1 demethylation, although tumors converting from negative to positive had a median decrease in LINE-1 methylation of 24%, compared to 6% in those not converting (P = 0.069). Five of 15 fully evaluable patients had reductions in tumor diameter (range 0.2% to 33.4%). Of these, three had simultaneous increases in three tumor suppressor genes (including the two patients with the greatest tumor regression) compared to 2 of 10 with tumor growth (P = 0.25). Conclusions In tumors with low tumor suppressor gene expression, decitabine may be associated with increased expression of the tumor suppressor genes FHIT, FUS1, and WWOX, but not PTEN.